2022
DOI: 10.1542/hpeds.2021-006507
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Practices and Implications in Young Infants With Urinary Tract Infection

Abstract: OBJECTIVES: Management of infants aged ≤60 days with urinary tract infections (UTI) is challenging. We examined renal imaging in infants aged ≤60 days with UTI at a tertiary care children’s hospital to identify the impact of standardizing renal ultrasound (RUS) interpretation. METHODS: We retrospectively studied infants aged ≤60 days hospitalized for UTI or fever with urine culture and renal imaging obtained and final diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This likely was an important source of heterogeneity as the use of a standard reporting criteria by radiologists has been associated with improved accuracy of identifying and classifying abnormalities. 58 Studies may have underreported minor abnormalities, thus, the pooled prevalence of abnormalities from this meta-analysis of 22.1% may be an underestimation. Subgroup analyses investigating heterogeneity found that an important study quality item related to the appropriate recruitment of study participants.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This likely was an important source of heterogeneity as the use of a standard reporting criteria by radiologists has been associated with improved accuracy of identifying and classifying abnormalities. 58 Studies may have underreported minor abnormalities, thus, the pooled prevalence of abnormalities from this meta-analysis of 22.1% may be an underestimation. Subgroup analyses investigating heterogeneity found that an important study quality item related to the appropriate recruitment of study participants.…”
Section: Discussionmentioning
confidence: 90%
“…Ultrasonography reporting of abnormalities across studies was not uniform, as no universally accepted standard exists. This likely was an important source of heterogeneity as the use of a standard reporting criteria by radiologists has been associated with improved accuracy of identifying and classifying abnormalities . Studies may have underreported minor abnormalities, thus, the pooled prevalence of abnormalities from this meta-analysis of 22.1% may be an underestimation.…”
Section: Discussionmentioning
confidence: 99%